2022
DOI: 10.1089/3dp.2020.0335
|View full text |Cite
|
Sign up to set email alerts
|

Design and System Considerations for Construction-Scale Concrete Additive Manufacturing in Remote Environments via Robotic Arm Deposition

Abstract: This work explores additive manufacturing (AM) of concrete by using a six-axis robotic arm and its use in large-scale, autonomous concrete construction. Concrete AM uses an extrusion method to deposit concrete beads in layers to create a three-dimensional (3D) shape. This method has been found to have many uses and advantages in construction applications. The lack of formwork and autonomous nature of this manufacturing method allows for new geometries and materials to be printed in unsafe or challenging enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In advanced manufacturing, robots are commonly used for tasks such as welding, printing, cutting, material handling, assembly, and inspection (Ding et al, 2015a;Djuric et al, 2016). They can operate in hazardous or challenging environments, reducing the risk to human operators (Meisel et al, 2022). In the nuclear industry, robots play a crucial role in handling hazardous or radioactive materials, performing maintenance tasks in radioactive environments, and supporting decommissioning activities (Sundar et al, 2012;Tsitsimpelis et al, 2019).…”
Section: Roboticsmentioning
confidence: 99%
“…In advanced manufacturing, robots are commonly used for tasks such as welding, printing, cutting, material handling, assembly, and inspection (Ding et al, 2015a;Djuric et al, 2016). They can operate in hazardous or challenging environments, reducing the risk to human operators (Meisel et al, 2022). In the nuclear industry, robots play a crucial role in handling hazardous or radioactive materials, performing maintenance tasks in radioactive environments, and supporting decommissioning activities (Sundar et al, 2012;Tsitsimpelis et al, 2019).…”
Section: Roboticsmentioning
confidence: 99%
“…The use of robotic systems in the construction industry can help improve efficiency, reduce labor costs, and enhance quality and performance [218]. Robotic systems can be used for a range of construction tasks, such as concrete placement [219], reinforcement installation [220], and formwork assembly [221], helping to streamline construction processes and ensure consistent quality and performance.…”
Section: Robotic Constructionmentioning
confidence: 99%
“…The development of the system required improvements in the system's movement, localization, and motion control for proper deposition. Meisel et al (2022) demonstrated a system for printing fully enclosed structures without much external support. The potential to use such a system in the intra-planetary civilization is explored, but it needed improvements in printing complex geometries.…”
Section: Large Scale Printingmentioning
confidence: 99%